How accurately do adult sons and daughters report and perceive parental deaths from coronary disease ?. Issue 11 (1st November 2000) - Watt, Graham; McConnachie, Alex; Upton, Mark; Emslie, Carol; Hunt, Kate
Abstract : OBJECTIVES: To describe how adult sons and daughters report and perceive parental deaths from heart disease DESIGN: Two generation family study. SETTING: West of Scotland. SUBJECTS: 1040 sons and 1298 daughters aged 30–59 from 1477 families, whose fathers and mothers were aged 45–64 in 1972–76 and have been followed up for mortality over 20 years. OUTCOME: Perception of a "family weakness" attributable to heart disease. RESULTS: 26% of sons and daughters had a parent who had died of coronary heart disease (CHD). The proportion was higher in older offspring (+18% per 10 year age difference) and in manual compared with non-manual groups (+37%). Eighty nine per cent of parental deaths from CHD were correctly reported by offspring. Only 23% of sons and 34% of daughters with at least one parent who had died of CHD considered that they had a family weakness attributable to heart disease. Perceptions of a family weakness were higher when one or both parents had died of CHD, when parental deaths occurred at a younger age, in daughters compared with sons and in offspring in non-manual compared with manual occupations. CONCLUSIONS: Only a minority of sons and daughters with experience of a parent having died from CHD perceive this in terms of a family weakness attributable to heart disease. Although men in manual occupations are most likely to develop CHD, they are least likely to interpret a parental death from CHD in terms of a family weakness. Health professionals giving advice to patients on their familial risks need to be aware of the difference between clinical definitions and lay perceptions of a family history of heart disease.